Myeloid Leukemia Methods and Protocols - Iland, Harry; Hertzberg, Mark.; Marlton, Paula; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2006)
The highly significant role that acquired genetic abnormalities play in the genesis, diagnosis, and management of hematological malignancies has become increasingly clear. Such abnormalities can serve as useful markers for initial diagnosis, accurate subclassification, and the evaluation of minimal residual disease, as well as providing critical targets for novel therapies. In Myeloid Leukemia: Methods and Protocols, a panel of internationally recognized research scientists and clinical investigators brings together a diverse collection of readily reproducible methods for identifying and quantifying a large number of specific genetic abnormalities associated with the broad spectrum of myeloid malignancies. The methods range from those that are of immediate clinical relevance to the investigation and management of patients with myeloid malignancies, to those that relate to recently identified genetic abnormalities of potential clinical significance. Highlights include techniques for the detection of BCR-ABL mutations and resistance to imatinib mesylate, detection of the FIP1L1-PDGFRA fusion in idiopathic hypereosinophilic syndrome and chronic eosinophilic leukemia, classification of AML by DNA-oligonucleotide microarrays, and detection of the V617F JAK2 mutation in myeloproliferative disorders. In addition to gene rearrangments, other prognostically relevant molecular lesions such as FLT3 mutations and WT-1 overexpression are covered. The protocols follow the successful Methods in Molecular Biology™ series format, each offering step-by-step laboratory instructions, an introduction outlining the principles behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Clinically relevant and highly practical, Myeloid Leukemia: Methods and Protocols offers cytogeneticists, hematologists, and oncologists cutting-edge laboratory techniques that can be rapidly implemented for the investigation and management of patients with myeloid malignancies.
Isolation of RNA and DNA From Leukocytes and cDNA Synthesis -- Cytogenetic and FISH Techniques in Myeloid Malignancies -- Overview of Real-Time RT-PCR Strategies for Quantification of Gene Rearrangements in the Myeloid Malignancies -- Diagnosis and Monitoring of Chronic Myeloid Leukemia by Qualitative and Quantitative RT-PCR -- Detection of BCR-ABL Mutations and Resistance to Imatinib Mesylate -- Deletion of the Derivative Chromosome 9 in Chronic Myeloid Leukemia -- Diagnosis and Monitoring of PML-RARA-Positive Acute Promyelocytic Leukemia by Qualitative RT-PCR -- Diagnosis and Monitoring of PML-RAR?-Positive Acute Promyelocytic Leukemia by Quantitative RT-PCR -- Diagnosis and Monitoring of AML1-MTG8 (ETO)-Positive Acute Myeloid Leukemia by Qualitative and Real-Time Quantitative RT-PCR -- Diagnosis and Monitoring of CBFB-MYH11-Positive Acute Myeloid Leukemia by Qualitative and Quantitative RT-PCR -- Detection of the FIP1L1-PDGFRA Fusion in Idiopathic Hypereosinophilic Syndrome and Chronic Eosinophilic Leukemia -- FLT3 Mutations in Acute Myeloid Leukemia -- WT-1 Overexpression in Acute Myeloid Leukemia and Myelodysplastic Syndromes -- Classification of AML by DNA-Oligonucleotide Microarrays -- Classification of AML Using a Monoclonal Antibody Microarray -- Methods for the Detection of the JAK2 V617F Mutation in Human Myeloproliferative Disorders -- Overexpression of PRV-1 Gene in Polycythemia Rubra Vera and Essential Thrombocythemia -- Chimerism Analysis Following Nonmyeloablative Stem Cell Transplantation.
Keywords: Hematology; Hematology